ASSESSING THE SOCIAL ANXIETY LEVEL CONCERNING SOCIAL MEDIA AND LIFE SATISFACTION OF UNIMAS STUDENTS - Jessica, Loh Seh Min (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Humans are now living in a digital era where most of the human activities such as exchanging information, building relationships, and communicating happen in the digital world. Therefore, human wellbeing in the physical world may be affected by their conditions in the virtual world. Therefore, this study aimed to examine the relationship of social anxiety concerning social media with life satisfaction among University Malaysia Sarawak (UNIMAS) students. A quantitative method was used in this research by distributing an online questionnaire to the target population, the UNIMAS students through social media platforms. The data collected was analyzed using the Pearson Correlation analysis and Independent Sample t-test. The results of the analysis showed that there was no correlation between the social anxiety level concerning social media and life satisfaction level among the UNIMAS students. Besides, there were no gender differences in the social anxiety level concerning social media and the life satisfaction level of the UNIMAS students. The results indicated that the usage of social media will not affect the students’ psychological wellbeing and life satisfaction negatively.